Evaluation of Consistency of Treatment Response Across Regions—the LEADER Trial in Relation to the ICH E17 Guideline - Nielsen, Henrik K.; DeChiaro, Stephanie; Goldman, Bryan (Frontiers in Medicine, 2021)
The US Food and Drug Administration in 2008 required new type 2 diabetes (T2D) medications to be subject to cardiovascular outcomes safety requirements. Accordingly, the global LEADER trial investigated cardiovascular outcomes of T2D treatment with liraglutide, a glucagon-like peptide-1 receptor agonist. LEADER (NCT01179048) was a multiregional clinical trial (MRCT) conducted from 2010 to 2016, thus completed before publication of the International Council for Harmonization (ICH) E17 guideline on MRCTs in 2017. Novo Nordisk pre-specified analysis of regional cardiovascular outcomes of LEADER participants. This paper assesses the pre-specified regional outcomes based on the ICH E17 guidelines on consistency evaluation. Regional LEADER participant numbers were broadly aligned with ICH E17 guidance and equally balanced across Europe, Asia, North America, and rest of the world. Overall primary major adverse cardiovascular events (MACE) composite outcome for the trial: hazard ratio (HR) (95% CI) 0.87 (0.78; 0.97); regional results varied, ranging from HR (95% CI) 0.62 (0.37; 1.04) (Asia) to 1.01 (0.84; 1.22) (North America). However, pre-specified Cox proportional-hazard regression analyses did not show clear evidence of interaction between regions and primary outcome (p = 0.20). Furthermore, post hoc analysis of the US population in the North American region found that adjusting for extrinsic or intrinsic factors did not account for this difference [HR (95% CI) 1.03 (0.84; 1.25)]. LEADER data evaluation demonstrated general consistency in cardiovascular safety across regions, except for US participants. Discrepancies in the North American region may relate to drug exposure or chance, but, as these were post hoc findings, the overall primary result is valid, aligned with ICH E17 guidelines.